Standaarde vir die maak van 'n gemeenskapsdiagnose - Marlene J. Viljoen; Marie E. Muller; Leana R. Uys (AOSIS, 1990)
Standards for the making o f a community diagnosis were formulated and validated on a national basis. These standards can be utilised by the community health nurse to improve the quality o f community diagnoses. The quality o f community diagnosis by community health nurses, was analysed by means o f a retrospective audit. Incomplete diagnosis were observed in the compilation o f a community profile and data resources were inadequately utilised. Important health indicators were not taken into account during the interpretation of data and planning strategies were incomplete. It appears as if the community health nurse tends to pay more attention to data that is readily available or can be utilised fo r quick results in his/her community planning.